2016
DOI: 10.1080/1068316x.2016.1168425
|View full text |Cite
|
Sign up to set email alerts
|

How to make perpetrators in denial disclose more information about their crimes

Abstract: This study examined interview techniques for eliciting admissions from perpetrators of a crime. Two techniques derived from the Strategic Use of Evidence (SUE) framework (SUE-Confrontation and SUE-Confrontation/Explain) were compared to an Early Disclosure of Evidence technique. Participants (N = 75) performed a mock criminal task divided into three phases before being interviewed. In the SUE conditions, statement-evidence inconsistencies were obtained by strategic interviewing for Phases 1 and 2. For both SUE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 25 publications
3
46
3
Order By: Relevance
“…In contrast to previous results (Tekin et al, 2016), no significant correlations were found within the individual SUE conditions. From this it seems that the suspects' overestimations about the critical phase of the crime were not the sole reason behind the amount of new information elicited.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous results (Tekin et al, 2016), no significant correlations were found within the individual SUE conditions. From this it seems that the suspects' overestimations about the critical phase of the crime were not the sole reason behind the amount of new information elicited.…”
Section: Discussioncontrasting
confidence: 99%
“…A further possible outcome of strategic evidence disclosure is the collection of new information. In recent years, laboratory‐based studies, examining the effect of evidence disclosure on eliciting admissions, found that if the available evidence was used strategically, admissions could be obtained from mock suspects about a critical phase of a crime for which information was lacking (Tekin et al, ; Tekin, Granhag, Strömwall, & Vrij, ). The interview tactic tested in these studies rested on the assumptions that (a) a suspect's perception of how much evidence the interviewer held would affect his or her counter‐interrogation strategies and (b) these counter‐interrogation strategies would affect what the suspect reveals or conceals during the interview.…”
Section: Introductionmentioning
confidence: 99%
“…The research into DRE began with the recognition of the different cognitive and interpersonal demands placed upon deceptive versus honest respondents (Colwell et al, 2002;Colwell et al, 2007;Mann & Vrij, 2006;Vrij, Granhag, Mann, & Leal, 2011). For example, deceptive respondents are required to provide enough information to satisfy the interviewer without making contradictions or releasing sensitive information (Ansarra et al, 2011;Colwell et al, 2013;Colwell, Hiscock-Anisman, Memon, Taylor, & Prewett, 2008;Hartwig, Granhag, & Strömwall, 2007;Hines et al, 2010;Tekin et al, 2015;Tekin, Granhag, Stromwall, & Vrij, 2016).…”
mentioning
confidence: 99%